Boosting the Lithium Storage Properties of a Flexible Li4Ti5O12/Graphene Fiber Anode via a 3D Printing Assembly Strategy - Chenpeng Zhao; Rui Wang; Biao Fang; Han Liang; Biyuan Nie; Ruyi Wang; Biao Xu; Songyang Feng; Ruqing Li; Shuaifei Li; Yuhui Xiong; Yuye Shao; et al. (Batteries, 2023)
Traditional lithium-ion batteries cannot meet the high flexibility and bendability requirements of modern flexible electronic devices due to the limitations of the electrode material. Therefore, the development of high-performance flexible energy storage devices is of great significance for promoting flexible electronics. In recent years, one-dimensional flexible fiber lithium-ion batteries have been rapidly developed due to their advantages of high flexibility and bendability. However, it remains highly challenging to realize 1D flexible fiber lithium-ion batteries with excellent electrochemical properties and good mechanical performance. In this work, a reduced graphene oxide-based printing ink is proposed for the fabrication of flexible Li4Ti5O12/graphene fiber electrodes using a 3D printing assembly strategy. It is noteworthy that the green reducing agent vitamin C was used to reduce the graphene oxide in one step, which improved the conductivity of the fiber electrode. Furthermore, a 3D conductive network was constructed inside the fiber electrodes due to the high specific surface area of the reduced graphene oxide, which enhanced the electronic conductivity and ion mobility. The fiber electrode not only exhibits good mechanical performance, but also has excellent electrochemical properties. Equally importantly, the method is simple and efficient, and the working environment is flexible. It can precisely control the shape, size and structure of the one-dimensional fiber flexible electrode, which is of great significance for the development of future flexible electronic devices.